La construcción de imaginarios Historia y cultura visual en Iberoamérica (1521-2021) - Prieto Ustio, Ester (Biblioteca Historia de América, 2022)
The artistic work, understood as a concept and a tangible object in any of its multiple technical and aesthetic categories, stands as an invaluable source of information, not only because of its intrinsic values, such as its formal characteristics, style or by whom it was created, among others. , but also for its ability to represent and make visible aspects of daily life, symbols of civil and religious power, beliefs, devotions and rites, historical events, social elements, feelings or connections between various plastic manifestations, transcending the limits of the merely artistic. until it becomes an object or artifact that encapsulates and preserves the culture, thought and concerns of a given time and a specific geographical space. This volume is made up of twenty-two papers by specialists participating in the Visual History and Culture Symposium, as well as others who have kindly accepted our invitation to share their studies. In the same way that the contributions collected are bidirectional between the New World and the Old Continent, their authors come from academic, cultural institutions and research centers located in the American and European space, making the relevance of these topics visible today through international level.